On three types of embedding of pseudowheels on the projective plane - Yang, Yan,; Liu, Yanpei, (Utilitas Mathematica, 2009)
A weak (or strong) embedding of a graph G is an embedding of G with no repeated edges (or vertices) on the boundary of each face of it. A pseudowheel is a wheel graph with multi-spokes. In this paper, we obtain the numbers (of equivalence classes) of three types of embedding, i.e., general embedding, weak embedding and strong embedding, of pseudowheels on the projective plane.